What is lim x = 0, [ (sqrt (1+ x) - 1 - x/2)/ x^2]

Expert Answers

An illustration of the letter 'A' in a speech bubbles

We have to find lim x-->0 [(sqrt (1+ x) - 1 - x/2)/ x^2]

Replacing x with 0, we see that the expression is of the form 0/0, or indeterminate. This allows us to use L'Hopital's Rule and derive the value of the limit by differentiating the denominator and the numerator.

lim x-->0 [(sqrt (1+ x) - 1 - x/2)/ x^2]

=> lim x-->0 [((1/2)*(1+ x)^(-1/2) - 1/2)/ 2x]

If we replace x with 0, this is again of the form 0/0, so we can differentiate the numerator and denominator again

=> lim x-->0 [ (-(1/4)(1 + x)^(-3/2)/2]

substituting x with 0 we get

(-(1/4)(1 + 0)^(-3/2)/2

=> [-(1/4)] / 2

=> [(-1/4)/2]

=> -1/8

The required value of the limit is -1/8

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial